Students' Perception Towards the Influence of YouTube Vlogs on Vocabulary Acquisition - Rahman, Nadya Septiani; Rafii, Muh.; Epa, Srilidiawati (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
YouTube vlogs have become a popular platform for entertainment and informal learning, particularly for English vocabulary acquisition among teenagers. With the growth of technology, YouTube vlogs have been freely accessed by students. This platform is not only a source of entertainment, but also a means of authentic language input. Several studies have discussed how YouTube vlogs can influence language acquisition. However, students’ perceptions of YouTube vlogs as a tool for vocabulary learning are rarely explored. Students' perceptions can be a strong basis for developing new language learning methods. Therefore, this study examined seventh-grade students’ perceptions of the influence of YouTube vlogs on vocabulary acquisition. At this stage, students are typically curious and receptive to various forms of media, making it possible to capture students’ early impressions and attitudes. Using a qualitative-descriptive method, data were collected through observations and Likert-scale questionnaires. This approach allowed the researchers to identify students’ behaviors and perceptions regarding the use of YouTube vlogs during the vocabulary learning process. The results indicate that students perceive YouTube vlogs as effective for improving vocabulary comprehension, pronunciation, and usage in daily life. Additionally, the findings reveal that students demonstrate high levels of motivation towards the YouTube vlogs as a vocabulary learning tool.